The Influence of the Level of Monovision upon Early Outcomes Following the Bilateral Implantation of an Enhanced Monovision Intraocular Lens - Richard N. McNeely; Stephen Stewart; Niraj Mandal; Salissou Moutari; Allon Barsam; Jonathan E. Moore (Vision, 2025)
This article provides an assessment of the impact of different levels of monovision upon early visual outcomes and quality of vision (QoV) following the bilateral implantation of enhanced monovision intraocular lenses (IOLs). Consecutive patients implanted bilaterally with the Rayone EMV (Rayner) were recruited. The dominant eye was targeted for emmetropia, and myopia was targeted in the nondominant eye. Patients were categorized based upon the postoperative refractive outcome in the nondominant eye as follows: Group A: −0.50 to −1.0 D (n = 40), Group B: <−1.00 = D (n = 46). Uncorrected distance (UDVA), intermediate (UIVA), and near (UNVA) visual acuity, and QoV were compared 3 months postoperatively. Binocular UIVA was 0.05 ± 0.10 and −0.01 ± 0.11logMAR (p = 0.03) in the two respective groups, and binocular UNVA was 0.23 ± 0.09 and 0.14 ± 0.09logMAR (p < 0.001). Day QoV was 8.77 ± 1.33 and 8.13 ± 1.34 for night QoV in group A, and 8.85 ± 0.99 and 7.85 ± 1.35, respectively, in group B. Group A had a lower spectacle independence rate of 55% compared to 89.1%. This IOL provides a satisfactory range of vision with high QoV satisfaction. A postoperative refractive error of −1.0 D or more in the nondominant eye significantly improves binocular UIVA, UNVA, and spectacle independence, without negatively impacting QoV.